THE IMPACT OF OPERANT BEHAVIORISM ON THE AUTHENTIC LEADER DEVELOPMENT - Ciroka, Ndricim (European Scientific Journal, ESJ, 2015)
This paper aims to analyze the relationship between the education of authentic leadership and the operant behavior of B. F. Skinner. The paper aims to demonstrate the concepts and distinctive aspects of operant conditioning in the progression of behavior modification and the education of authentic leadership. This paper gives an approach of where to go and what can be achieved through the method of operant conditioning of Skinner. The concrete and practical implementation of this theory in the education and development of authentic leaders, is based majorly on the researches and work carried out by Bruce J. Avolio. Taking into consideration the fact that the authentic leader is based associated with positive experiences and reinforcements, we have another reason to relate the operant behaviorism with the authentic leader.